Repurposing antimicrobial stewardship tools in the electronic medical record for the management of COVID-19 patients. (8th November 2020) - Davis, Matthew W.; McManus, Dayna; Koff, Alan; Jaszczur, Gregory R.; Malinis, Maricar; Dela Cruz, Charles; Britto, Clemente J.; Price, Christina; Azmy, Veronica; Kaman, Kelsey; Gaston, David; Early, Kevin; et al.
Abstract: During the COVID-19 pandemic, the antimicrobial stewardship module in our electronic medical record was reconfigured for the management of COVID-19 patients. This change allowed our subspecialist providers to review charts quickly to optimize potential therapy and management during the patient surge.